Eksplorasi Implementasi Program Pelatihan dan Pengembangan dalam Meningkatkan Kompetensi Peserta di Lembaga Pelatihan Kerja Mutiara Bawen - Lestari, Novianni Indri; Maryani, Tri (Mahesa Research Center, 2025)
This study explores the implementation of training and development programs at the Mutiara Bawen Vocational Training Center (LPK) and their impact on participants' competencies. The study focuses on the application of Competency-Based Training (CBT) to enhance both technical and non-technical skills, as well as the factors that support or hinder training effectiveness. Data were collected through in-depth interviews, observations, and document reviews, then analyzed qualitatively using the interactive model of Miles and Huberman. The results indicate that the training was systematically conducted through four stages: needs analysis, curriculum design, theory-practice implementation (30%–70%), and learning outcome evaluation (Kirkpatrick Levels 1–3). The program successfully increased technical skills by 36.6% and non-technical skills by 25%, with 65% of participants securing employment at partner companies within six months. Training effectiveness was influenced by training facilities, instructor-to-participant ratio, instructor quality, participant motivation, and industry involvement. The findings underscore the importance of synergy among training institutions, industry, and government to develop a training ecosystem that is adaptive to the demands of Industry 4.0.